A Trisectrix From a Carpenter's Square. Issue 1 (1st February 2017) - Richeson, David
Summary: In 1928, Henry Scudder described how to use a carpenter's square to trisect an angle. We use the ideas behind Scudder's technique to define a trisectrix—a curve that can be used to trisect an angle. We also describe a compass that could be used to draw the curve.